Representasi Stigmatisasi Korea Utara oleh Masyarakat Korea Selatan Melalui Drama Seri Extraordinary Attorney Woo - Femisyah, Jazzy Tiara; Azeharie, Suzy (Koneksi, 2023)
The prolonged war between South Korea and North Korea has stigmatised the North Korean community or defectors. It is not uncommon for North Korean defectors who are in South Korea to receive different treatment from local residents. This is also depicted in several Korean drama series, one of which is the sixth episode of Extraordinary Attorney Woo. This research examines the signs contained in several scenes that represent the stigmatisation of North Korean society. This research uses a qualitative approach with discourse analysis as the data collection method. The subject of this research is the sixth episode of Extraordinary Attorney Woo. The representation of stigmatisation of South Korean society towards North Korea as the object is studied with Charles Sander Pierce's semiotics. The results show that the drama series Extraordinary Attorney Woo has signs that can be interpreted into a message associated with mass communication theory with the function of entertainment and cultural transformation. The interpretant in this drama is the stigmatisation of North Korean defectors depicted in several scenes. In addition to interpreting stigmatisation, there is also a deconstruction of meaning illustrated by the defence given by the main character. Perang berkepanjangan yang terjadi antara Korea Selatan dan Korea Utara menimbulkan stigma terhadap masyarakat atau pembelot Korea Utara. Tidak jarang pula pembelot Korea Utara yang berada di Korea Selatan mendapat perlakuan berbeda dari warga setempat. Hal ini juga digambarkan dalam beberapa drama seri Korea, salah satunya drama seri Extraordinary Attorney Woo episode keenam. Penelitian ini mengkaji tanda-tanda yang terdapat dalam beberapa adegan yang merepresentasikan stigmatisasi terhadap masyarakat Korea Utara. Penelitian ini menggunakan pendekatan kualitatif dengan analisis wacana sebagai metode pengumpulan data. Subjek dari penelitian ini adalah drama Extraordinary Attorney Woo episode keenam. Representasi stigmatisasi masyarakat Korea Selatan terhadap Korea Utara sebagai objeknya dikaji dengan semiotika Charles Sander Pierce. Hasil menunjukkan bahwa drama seri Extraordinary Attorney Woo memiliki tanda-tanda yang dapat diinterpretasikan menjadi sebuah pesan yang dikaitkan dengan teori komunikasi massa dengan fungsi hiburan dan transformasi budaya. Interpretant dalam drama ini adalah adanya stigmatisasi terhadap pembelot Korea Utara yang digambarkan dalam beberapa adegan. Selain menginterpretasikan stigmatisasi, juga terdapat dekonstruksi makna yang digambarkan dengan pembelaan yang diberikan pemeran utama.